High-strength pouring type polyurethane elastomer and preparation method thereof
By using specific raw materials and composite technologies in polyurethane elastomers to form a crosslinking network and uniform dispersion composite, the limitations of traditional polyurethane elastomers in terms of strength, heat resistance and chemical resistance are solved, and the effects of high strength, good flexibility and extreme environment resistance are achieved.
Patent Information
- Application Number
- CN202510172776.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional polyurethane elastomers have limitations in strength, heat resistance and chemical resistance, and are difficult to meet the application needs in high-strength and extreme environments.
The polyester polyol, catalyst, plasticizer, chain extender, adipic acid, diisocyanate and other raw materials are used, and the reinforcement, wear-resistant filler, weathering agent and antioxidant are combined to improve the strength, heat resistance and chemical resistance of the polyurethane elastomer through the formation of the cross-linking network and the dispersion of the composite.
It realizes the high strength, good flexibility, heat resistance and chemical resistance of polyurethane elastomers, extends the service life of the material, and expands its application range in extreme environments.
Smart Images

Figure BDA0005274532160000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials, and more specifically, to a high-strength cast polyurethane elastomer and a preparation method thereof. Background Art
[0002] Polyurethane elastomers, with their excellent elasticity, wear resistance, tear resistance and outstanding processability, play a vital role in many fields, from footwear manufacturing and furniture decoration in daily life to seals and shock-absorbing materials in the industrial field, and to high-end aerospace and automobile manufacturing. The application of polyurethane elastomers is everywhere. However, despite its wide range of applications, traditional polyurethane elastomers still have obvious limitations in terms of strength, heat resistance and chemical resistance.
[0003] In terms of strength, traditional polyurethane elastomers are prone to deformation or breakage under high loads or long-term stress, which limits their application in heavy-load or high-strength applications. In terms of heat resistance, when the ambient temperature rises, the molecular chain movement of the polyurethane elastomer intensifies, causing the material to soften and the mechanical properties to deteriorate, making it unable to meet the requirements of use in high-temperature environments. In addition, in the face of erosion by chemicals such as acids, alkalis, and organic solvents, the chemical resistance of traditional polyurethane elastomers is also insufficient, which can easily lead to material aging and performance degradation.
[0004] Especially in extreme environments, such as high temperature, high pressure, highly corrosive media and other harsh conditions, the performance of traditional polyurethane elastomers often cannot meet the requirements of specific fields, which seriously restricts the expansion of their application scope.
[0005] Therefore, how to prepare a new polyurethane elastomer that has the advantages of good flexibility, good elasticity, high strength, good heat resistance, good chemical resistance, good wear resistance and good tear resistance is a problem to be solved. Summary of the invention
[0006] In order to prepare a new polyurethane elastomer that has the advantages of good flexibility, good elasticity, high strength, good heat resistance, good chemical resistance, good wear resistance and good tear resistance, it is a problem to be solved. The present application provides a high-strength cast polyurethane elastomer and a preparation method thereof.
[0007] In the first aspect, the present application provides a high-strength cast polyurethane elastomer, adopting the following technical scheme: a high-strength cast polyurethane elastomer, comprising the following raw materials in parts by weight: 85-100 parts of polyester polyol, 0.5-1 part of catalyst, 2-5 parts of plasticizer, 2-5 parts of chain extender, 2-5 parts of reinforcing agent, 1-3 parts of wear-resistant filler, 30-50 parts of diisocyanate, 1-2 parts of adipic acid ester, 5-10 parts of ethanol, 0.5-1 part of weathering agent, and 0.5-1 part of antioxidant.
[0008] By adopting the above technical scheme, polyester polyols, catalysts, plasticizers, chain extenders, adipic acid esters, and diisocyanates are used to promote the formation of a polyurethane cross-linking network, so that the polyurethane elastomer has good flexibility, elasticity and chemical corrosion resistance; the filling and dispersion effects of reinforcing agents and wear-resistant fillers are combined to further improve the strength, wear resistance, heat resistance and tear resistance of the polyurethane elastomer; and weathering agents and antioxidants are combined to further improve the weather resistance of the polyurethane elastomer and extend the service life of the polyurethane elastomer.
[0009] Preferably, the reinforcing agent is composed of a magnesium oxide sand composite and a diatomaceous earth sand composite in a mass ratio of 1:1-2.
[0010] By adopting the above technical scheme, the magnesium oxide sand composite and the diatom sand composite are matched, and the dispersing effect of the composite is utilized to facilitate uniform dispersion in the polyester polyol, and the problems of agglomeration and aggregation are not easy to occur, which affects the strength and wear resistance uniformity of the polyurethane elastomer; the hydroxyl groups of the cellulose nanocrystals themselves and the hydroxyl groups on the surface of the diatom sand are matched, and the polyester polyol and diisocyanate are further adsorbed and cross-linked with them, thereby improving the arrangement and orientation of the polyurethane molecular chains, increasing the density and connection effect of the cross-linking network, and matching the needle-like flexibility of the cellulose nanocrystals and the strength of the diatom sand, so as to further improve the flexibility and strength of the polyurethane elastomer.
[0011] When poured into the mold for molding, the molecular chain cross-linking and expansion are prone to volume expansion problems. The flexible deformation of cellulose nanocrystals combined with the porous structure and strength of diatom sand can further alleviate the expansion. After the reaction, the volume gradually shrinks, and the cross-linked network formed by cellulose nanocrystals, diatom sand, polyester polyols and other substances further resists the shrinkage force, thereby ensuring the molding quality of the polyurethane elastomer; combined with the porous structure and elastic cross-linked network of diatom sand, it absorbs external impact force and improves the impact resistance of the polyurethane elastomer; at the same time, diatom sand also has good thermal conductivity, which can achieve uniform curing inside and outside, and is not prone to the problem of slow internal curing and complete surface curing of the polyurethane elastomer, further ensuring the molding quality of the polyurethane elastomer.
[0012] Preferably, the magnesia sand composite is prepared by loading magnesia sand with polyethylene glycol solution and cellulose nanocrystals and then bonding with cetearyl alcohol solution, and the mass ratio of magnesia sand, polyethylene glycol solution, cellulose nanocrystals and cetearyl alcohol solution is 1:0.1-0.2:0.05-0.1:0.15-0.3.
[0013] By adopting the above technical scheme, the magnesium oxide sand has a large density and surface area. After the cellulose nanocrystals are loaded, the cellulose nanocrystals are distributed on the surface of the magnesium oxide sand particles. When the reinforcing agent is added to the polyester polyol and mixed, it can be evenly dispersed, and it is not easy to have problems such as uneven dispersion, agglomeration, and floating due to the nano-scale particle size of the cellulose nanocrystals, which affects the uniformity of the distribution of the reinforcing agent in the cast polyurethane elastomer; finally, the surface is bonded with cetearyl alcohol, and the fatty alcohol structure of cetearyl alcohol can promote the polyurethane molecular chain to have a higher degree of rotational freedom, thereby more flexible movement, and improve the flexibility and elasticity of the polyurethane elastomer; and the dispersion effect of cetearyl alcohol and the hydroxyl groups in cetearyl alcohol and cellulose nanocrystals are combined to further improve the structural density of the polyurethane cross-linked network. With the cross-linking effect of cellulose nanocrystals and polyurethane on the surface of the magnesium oxide sand, the strength of the magnesium oxide sand and the crystalline structure of cetearyl alcohol can form a microcrystalline area in the polyurethane, further improving the flexibility, strength and wear resistance of the polyurethane elastomer.
[0014] Preferably, the average length of the cellulose nanocrystals is 80-200 nm, and the average particle size of the magnesia sand composite is 5-10 μm.
[0015] By adopting the above technical scheme, the size of cellulose nanocrystals and the size of magnesia sand composites are limited. In the raw material mixing stage, the magnesia sand composites are ensured to be evenly dispersed and the problem of nano-agglomeration is not easy to occur. In the curing stage, the evenly dispersed cellulose nanocrystals can be cross-linked with polyester polyols, isocyanates and other substances, thereby promoting the formation of a cross-linked network; combined with the long fiber structure of cellulose nanocrystals, more orientation and freedom can be improved, thereby improving the flexibility, elasticity and strength of the polyurethane elastomer.
[0016] Preferably, the diatom sand composite is prepared from diatom sand, N-hydroxysuccinimide composite liquid and polyetheretherketone particles in a mass ratio of 1:0.5-1:0.2-0.5.
[0017] By adopting the above technical scheme, the surface of diatom sand is bonded with polyetheretherketone particles via N-hydroxysuccinimide composite liquid, and the good flexibility and elasticity of polyetheretherketone are utilized to increase the flexibility and elasticity of the diatom sand composite, and the amide group and hydroxyl group of N-hydroxysuccinimide are utilized to introduce new cross-linking points, thereby enhancing the mechanical strength and flexibility of the polyurethane elastomer, and N-hydroxysuccinimide can also improve the heat resistance of the polyurethane elastomer; combined with the strength of the diatom sand, the polyurethane elastomer has the advantages of high strength and high elasticity.
[0018] Preferably, the N-hydroxysuccinimide composite liquid is prepared from N-hydroxysuccinimide, propolis and ethanol in a mass ratio of 1:0.2-0.5:90-110.
[0019] By adopting the above technical scheme, N-hydroxysuccinimide and propolis are both dissolved in ethanol, and the viscosity of propolis is utilized to improve the viscosity of the N-hydroxysuccinimide composite liquid, so that polyetheretherketone can be easily adhered to the surface of diatom sand. In addition, the melting point of propolis is about 65°C. During the casting process, propolis can also be hot-melted, and the cross-linking effect of N-hydroxysuccinimide with polyether polyols and isocyanates can be combined to further improve the cross-linking density and stability of the polyurethane elastomer, thereby improving the strength, flexibility and impact resistance of the polyurethane elastomer.
[0020] Preferably, the wear-resistant filler is prepared by polycaprolactone particles loaded with silicon carbide powder and alumina powder in a mass ratio of 1:0.5-1:0.5-1, the average particle size of the silicon carbide powder and the alumina powder is 100-500nm, and the average particle size of the polycaprolactone particles is 10-20μm.
[0021] By adopting the above technical scheme, polycaprolactone particles are loaded with silicon carbide and aluminum oxide. The nanoscale structure of silicon carbide and aluminum oxide can not only improve the strength and impact resistance of the polyurethane elastomer, but also silicon carbide and aluminum oxide have certain thermal conductivity and heat resistance. During the casting process, the internal and external curing can be uniform as much as possible, so that the polyurethane elastomer has better molding quality.
[0022] The particle size of polycaprolactone particles is limited to be relatively large, and the particle sizes of silicon carbide powder and alumina powder are nanometer-level, so that the wear-resistant filler is evenly dispersed when the raw materials are mixed; after pouring into the mold, under the condition that the mold temperature reaches the melting point of polycaprolactone, the polycaprolactone is hot-melted to separate the silicon carbide powder and alumina powder, and while polycaprolactone participates in cross-linking, the silicon carbide powder and alumina powder play a filling effect, further improving the flexibility and strength of the polyurethane elastomer.
[0023] Preferably, the chain extender is composed of 1,4-butanediol and zinc-based tridecanol in a mass ratio of 1:0.5-1.
[0024] By adopting the above technical scheme, 1,4-butanediol and zinc-tridecyl alcohol are mainly used as linear chain extenders in polyurethane. The hydroxyl groups they contain can react with the isocyanate groups in the polyurethane prepolymer, thereby extending the molecular chain of the polyurethane and improving the mechanical properties and thermal stability of the polyurethane.
[0025] Preferably, the catalyst is composed of dibutyltin dilaurate and triethanolamine in a mass ratio of 1:0.2-0.4.
[0026] By adopting the above technical solution, dibutyltin dilaurate and triethanolamine are combined to promote the cross-linking reaction of polyurethane, enhance the flexibility and elasticity of polyurethane elastomer, and improve the strength and wear resistance.
[0027] In a second aspect, the present application provides a method for preparing a high-strength cast polyurethane elastomer, using the following technical solution: A method for preparing a high-strength cast polyurethane elastomer comprises the following steps: S1, mixing polyester polyol, adipic acid ester and ethanol and stirring evenly to obtain a primary mixture; S2, adding diisocyanate, catalyst, plasticizer and chain extender to the primary mixture, treating at 50-55°C for 1-3h, and finally adding wear-resistant filler, reinforcing agent, weathering agent and antioxidant, mixing and stirring evenly to obtain a casting material; S3. The casting mold is preheated to 65-70° C., the casting material is poured into the casting mold, and the casting material is kept warm and cured for 1-2 hours, and then cooled to room temperature to obtain a finished polyurethane elastomer.
[0028] By adopting the above technical scheme, during the preparation of the polyurethane elastomer, the polycaprolactone is not easy to melt at 50-55°C, thereby ensuring the existence of the composite. At 65-70°C, the polycaprolactone melts, causing the cellulose nanocrystals, silicon carbide and alumina to disintegrate and disperse. During the mixing of the raw materials, the reinforcing agent and the wear-resistant filler are ensured to be evenly dispersed. During the curing process, the evenly dispersed filling effect is ensured, thereby improving the flexibility, strength, wear resistance and impact resistance of the polyurethane elastomer.
[0029] In summary, this application has the following beneficial effects: 1. Use polyester polyols, catalysts, plasticizers, chain extenders, adipic acid esters, and diisocyanates to promote the formation of polyurethane cross-linking networks, so that polyurethane elastomers have good flexibility, elasticity, and chemical corrosion resistance; with the filling and dispersion effects of reinforcing agents and wear-resistant fillers, the strength, wear resistance, heat resistance, and tear resistance of polyurethane elastomers can be further improved; and with weathering agents and antioxidants, the weather resistance of polyurethane elastomers can be further improved and the service life of polyurethane elastomers can be extended.
[0030] 2. The melting points of polyethylene glycol 8000 and polycaprolactone are at 60°C. During the mixing of raw materials, hot melting is not easy to occur, which ensures that the reinforcing agent and wear-resistant filler have a good particle size, is easy to be evenly dispersed, and is not easy to have the problem of nano-level powder agglomeration. During the casting process, at 65-70°C, they can gradually hot melt and make the nano-level cellulose nanocrystals, silicon carbide powder, and alumina powder evenly dispersed and cross-linked in the polyurethane network structure, thereby improving the strength, flexibility, elasticity and wear resistance of the polyurethane elastomer.
[0031] 3. The magnesium oxide sand composite and the diatom sand composite are matched with each other, and the micron-level dispersion effect of the composite is utilized to facilitate uniform dispersion in the polyester polyol, and the problem of nano-level particle size agglomeration and aggregation is not easy to occur, which affects the strength and wear resistance uniformity of the polyurethane elastomer; the hydroxyl groups of the cellulose nanocrystals themselves and the hydroxyl groups on the surface of the diatom sand are combined to further adsorb the polyester polyol and the diisocyanate to react with them to improve the arrangement and orientation of the polyurethane molecular chains, and to increase the density and connection effect of the cross-linking network. The needle-like flexibility of the cellulose nanocrystals and the strength of the diatom sand are combined to further improve the flexibility and strength of the polyurethane elastomer. DETAILED DESCRIPTION
[0032] The present application is further described in detail below with reference to the embodiments.
[0033] Preparation example of magnesia sand composite The following raw materials are all commercially available.
[0034] Preparation Example 1: The magnesium oxide sand composite is prepared by the following method: 0.15 kg of polyethylene glycol liquid is evenly sprayed on the surface of 1 kg of magnesium oxide sand, the average particle size of the magnesium oxide sand is 3 μm, the polyethylene glycol liquid is a polyethylene glycol aqueous solution with a mass fraction of 15%, and the polyethylene glycol is polyethylene glycol 8000, and then 0.1 kg of cellulose nanocrystals are added, and the average length of the cellulose nanocrystals is 100 nm. Then 0.2 kg of cetearyl alcohol liquid is evenly sprayed, and the cetearyl alcohol liquid is a cetearyl alcohol ethanol solution with a mass fraction of 10%. After drying and breaking up, a magnesium oxide sand complex is obtained, and the average particle size of the magnesium oxide sand complex is 8 μm.
[0035] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 0.1 kg of polyethylene glycol liquid is evenly sprayed on the surface of 1 kg of magnesium oxide sand, and the average particle size of the magnesium oxide sand is 5 μm. Then 0.05 kg of cellulose nanocrystals are added, and the average length of the cellulose nanocrystals is 200 nm. Then 0.15 kg of cetearyl alcohol liquid is evenly sprayed, and the cetearyl alcohol liquid is a 10% by mass cetearyl alcohol ethanol solution. After drying and breaking up, a magnesium oxide sand complex is obtained, and the average particle size of the magnesium oxide sand complex is 10 μm.
[0036] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: 0.2 kg of polyethylene glycol liquid is evenly sprayed on the surface of 1 kg of magnesium oxide sand, and the average particle size of the magnesium oxide sand is 2 μm. Then 0.1 kg of cellulose nanocrystals are added, and the average length of the cellulose nanocrystals is 80 nm. Then 0.3 kg of cetearyl alcohol liquid is evenly sprayed, and the cetearyl alcohol liquid is a 10% by mass cetearyl alcohol ethanol solution. After drying and breaking up, a magnesium oxide sand complex is obtained, and the average particle size of the magnesium oxide sand complex is 5 μm.
[0037] Preparation example of diatom sand composite Among the following raw materials, N-hydroxysuccinimide was purchased from Jiangsu Bosite Chemical Technology Co., Ltd.; other raw materials were all commercially available.
[0038] Preparation Example 4: The diatom sand composite is prepared by the following method: 1 kg of N-hydroxysuccinimide and 0.35 kg of propolis were placed in 100 kg of ethanol, wherein the ethanol was anhydrous ethanol with a mass fraction of 99%, and stirred and mixed at a speed of 250 r / min for 30 minutes to obtain an N-hydroxysuccinimide composite liquid; 0.7 kg of N-hydroxysuccinimide composite liquid was evenly sprayed on the surface of 1 kg of diatom sand, and then 0.3 kg of polyetheretherketone particles were added. The average particle size of the polyetheretherketone particles was 2 μm, and the average particle size of the diatom sand was 8 μm. After drying and breaking up, a diatom sand complex was obtained. The average particle size of the diatom sand complex was 15 μm.
[0039] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 1 kg of N-hydroxysuccinimide and 0.2 kg of propolis are placed in 90 kg of ethanol, wherein the ethanol is anhydrous ethanol with a mass fraction of 99%, and stirred and mixed at a speed of 250 r / min for 30 minutes to obtain an N-hydroxysuccinimide composite liquid; 0.5 kg of N-hydroxysuccinimide composite liquid was evenly sprayed on the surface of 1 kg of diatom sand, and then 0.2 kg of polyetheretherketone particles were added. The average particle size of the polyetheretherketone particles was 2 μm, and the average particle size of the diatom sand was 8 μm. After drying and breaking up, a diatom sand complex was obtained. The average particle size of the diatom sand complex was 15 μm.
[0040] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 1 kg of N-hydroxysuccinimide and 0.5 kg of propolis are placed in 110 kg of ethanol, wherein the ethanol is anhydrous ethanol with a mass fraction of 99%, and stirred and mixed at a speed of 250 r / min for 30 minutes to obtain an N-hydroxysuccinimide composite liquid; 1 kg of N-hydroxysuccinimide composite liquid was evenly sprayed on the surface of 1 kg of diatom sand, and then 0.5 kg of polyetheretherketone particles were added, the average particle size of the polyetheretherketone particles was 2 μm, and the average particle size of the diatom sand was 8 μm. After drying and breaking up, a diatom sand complex was obtained, and the average particle size of the diatom sand complex was 15 μm.
[0041] Preparation example of wear-resistant filler The following raw materials are all commercially available.
[0042] Preparation Example 7: Wear-resistant filler is prepared by the following method: 1 kg of polycaprolactone particles were mixed with 0.7 kg of silicon carbide powder and 0.8 kg of alumina powder and stirred evenly, then heated to 65°C and stirred for 30 seconds. After stirring and dispersion, a wear-resistant filler was obtained; the average particle size of the polycaprolactone particles was 15 μm, and the average particle sizes of the silicon carbide powder and the alumina powder were 300 nm. The finished wear-resistant filler was sieved through a 600-mesh sieve.
[0043] Preparation Example 8: This preparation example differs from Preparation Example 7 in that: 1 kg of polycaprolactone particles were mixed with 0.5 kg of silicon carbide powder and 0.5 kg of alumina powder and stirred evenly, then heated to 65°C and stirred for 30 seconds. After stirring and dispersion, a wear-resistant filler was obtained; the average particle size of the polycaprolactone particles was 20 μm, and the average particle size of the silicon carbide powder and the alumina powder was 500 nm. The finished wear-resistant filler was sieved through a 400-mesh sieve.
[0044] Preparation Example 9: This preparation example differs from Preparation Example 7 in that: 1 kg of polycaprolactone particles were mixed with 1 kg of silicon carbide powder and 1 kg of alumina powder and stirred evenly, then heated to 65°C and stirred for 30 seconds. After stirring and dispersion, a wear-resistant filler was obtained; the average particle size of the polycaprolactone particles was 10 μm, and the average particle sizes of the silicon carbide powder and the alumina powder were 100 nm. The finished wear-resistant filler was sieved through a 600-mesh sieve. Example
[0045] Among the following raw materials, polyester polyol was purchased from Shandong Huibang New Material Technology Co., Ltd.; ultraviolet absorber UV-1 was purchased from Nanjing Milan Chemical Co., Ltd.; other raw materials were all commercially available.
[0046] Example 1: A high-strength cast polyurethane elastomer: 90kg of polyester polyol, 1kg of catalyst, 4kg of plasticizer, 3kg of chain extender, 3kg of reinforcing agent, 2kg of wear-resistant filler, 40kg of diisocyanate, 1.5kg of adipic acid ester, 8kg of ethanol, 1kg of weathering agent, and 0.5kg of antioxidant; the catalyst is composed of dibutyltin dilaurate and triethanolamine in a mass ratio of 1:0.3; the plasticizer is phthalate; the chain extender is composed of 1,4-butanediol and zinc-based tridecanol in a mass ratio of 1:1.5; the reinforcing agent is composed of a cellulose nanocrystal complex prepared in Preparation Example 1 and a diatomaceous earth complex prepared in Preparation Example 4 in a mass ratio of 1:1; the wear-resistant filler is the wear-resistant filler prepared in Preparation Example 7; the mass fraction of ethanol is 75%, the weathering agent is an ultraviolet absorber UV-1, and the antioxidant is 2,6-di-tert-butyl-4-methylphenol; the preparation method is as follows: S1, mixing polyester polyol, adipic acid ester and ethanol and stirring evenly to obtain a primary mixture; S2, adding diisocyanate, catalyst, plasticizer and chain extender to the primary mixture, treating at 50°C for 2h, and finally adding wear-resistant filler, reinforcing agent, weathering agent and antioxidant, mixing and stirring evenly to obtain a casting material; S3. The casting mold is preheated to 65° C., the casting material is poured into the casting mold, and the curing reaction is carried out for 2 hours, and then cooled to room temperature to obtain a finished polyurethane elastomer.
[0047] Embodiment 2: This embodiment differs from Embodiment 1 in that: 85kg of polyester polyol, 0.5kg of catalyst, 2kg of plasticizer, 2kg of chain extender, 2kg of reinforcing agent, 1kg of wear-resistant filler, 30kg of diisocyanate, 1kg of adipic acid ester, 5kg of ethanol, 0.5kg of weathering agent, and 0.5kg of antioxidant; the catalyst is composed of dibutyltin dilaurate and triethanolamine in a mass ratio of 1:0.2; the plasticizer is phthalate; the chain extender is composed of 1,4-butanediol and zinc-based tridecanol in a mass ratio of 1:0.5; the reinforcing agent is composed of a cellulose nanocrystal complex prepared in Preparation Example 2 and a diatomaceous earth complex prepared in Preparation Example 5 in a mass ratio of 1:1; the wear-resistant filler is the wear-resistant filler prepared in Preparation Example 8; the preparation method is as follows: S1, mixing polyester polyol, adipic acid ester and ethanol and stirring evenly to obtain a primary mixture; S2, adding diisocyanate, catalyst, plasticizer and chain extender to the primary mixture, treating at 50°C for 3h, and finally adding wear-resistant filler, reinforcing agent, weathering agent and antioxidant, mixing and stirring evenly to obtain a casting material; S3. The casting mold is preheated to 65° C., the casting material is poured into the casting mold, and the curing reaction is carried out for 2 hours, and then cooled to room temperature to obtain a finished polyurethane elastomer.
[0048] Embodiment 3: This embodiment differs from Embodiment 1 in that: 100kg of polyester polyol, 1kg of catalyst, 5kg of plasticizer, 5kg of chain extender, 5kg of reinforcing agent, 3kg of wear-resistant filler, 50kg of diisocyanate, 2kg of adipic acid ester, 10kg of ethanol, 1kg of weathering agent, and 1kg of antioxidant; the catalyst is composed of dibutyltin dilaurate and triethanolamine in a mass ratio of 1:0.4; the plasticizer is phthalate; the chain extender is composed of 1,4-butanediol and zinc-based tridecanol in a mass ratio of 1:1; the reinforcing agent is composed of a cellulose nanocrystal complex prepared in Preparation Example 3 and a diatomaceous earth complex prepared in Preparation Example 6 in a mass ratio of 1:2; the wear-resistant filler is the wear-resistant filler prepared in Preparation Example 9; The preparation method is as follows: S1, mixing polyester polyol, adipic acid ester and ethanol and stirring evenly to obtain a primary mixture; S2, adding diisocyanate, catalyst, plasticizer and chain extender to the primary mixture, treating at 55°C for 1h, and finally adding wear-resistant filler, reinforcing agent, weathering agent and antioxidant, mixing and stirring evenly to obtain a casting material; S3. The casting mold is preheated to 70° C., the casting material is poured into the casting mold, and the curing reaction is carried out for 1 hour, and then cooled to room temperature to obtain a finished polyurethane elastomer.
[0049] Embodiment 4: This embodiment differs from Embodiment 1 in that: In the enhancer, the magnesia sand complex is replaced by magnesia sand of equal mass, and the diatom sand complex is replaced by diatom sand of equal mass, and the particle sizes of the magnesia sand and the diatom sand are 100 nm.
[0050] Embodiment 5: This embodiment differs from Embodiment 1 in that: No cellulose nanocrystals and polyethylene glycol solution were added during the preparation of the magnesium oxide sand composite in the enhancer.
[0051] Embodiment 6: This embodiment differs from Embodiment 1 in that: No cetearyl alcohol solution was added during the preparation of the magnesium oxide sand complex in the enhancer.
[0052] Embodiment 7: This embodiment differs from Embodiment 1 in that: No polyetheretherketone particles were added during the preparation of the diatomaceous earth composite in the enhancer.
[0053] Embodiment 8: This embodiment differs from Embodiment 1 in that: The wear-resistant fillers are silicon carbide powder and aluminum oxide powder, and no polycaprolactone particles are added.
[0054] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: No reinforcing agents or wear-resistant fillers are added to the raw materials.
[0055] Performance testing 1. Strength and flexibility testing Polyurethane elastomers were prepared by the methods of Examples 1-8 and Comparative Example 1, respectively, and the tensile strength and elongation at break were tested with reference to GB / T528-2009, and the data were recorded.
[0056] 2. Elasticity testing The polyurethane elastomers were prepared by the methods of Examples 1-8 and Comparative Example 1, and the rebound rate was tested with reference to GB / T1681-2009, and the data were recorded.
[0057] 3. Wear resistance test The polyurethane elastomers were prepared by the methods of Examples 1-8 and Comparative Example 1, respectively, and the wear amount was detected and the data was recorded with reference to GB / T5865-2008 Determination of wear resistance of vulcanized rubber or thermoplastic rubber.
[0058] 4. Heat resistance test Polyurethane elastomers were prepared by the methods of Examples 1-8 and Comparative Example 1, respectively, and placed at 90° C. for 30 min. The tensile strength was tested according to GB / T528-2009, and the data were recorded.
[0059] Table 1 Performance test table It can be seen from Examples 1-3 and Table 1 that the polyurethane elastomer prepared in the present application has high strength, good flexibility, good heat resistance, good elasticity and resilience, and good wear resistance.
[0060] It can be seen from Example 1 and Examples 4-8 in combination with Table 1 that in the enhancer of Example 4, the magnesia sand composite is replaced with the magnesia sand of equal mass, and the diatom sand composite is replaced with the diatom sand of equal mass. Compared with Example 1, the tensile strength of the elastomer prepared in Example 4 is lower than that in Example 1, the elongation at break is lower than that in Example 1, the rebound rate is lower than that in Example 1, and the abrasion amount is higher than that in Example 1; it indicates that the presence of the magnesia sand composite and the diatom sand composite can not only cross-link polyester polyols and isocyanates, and improve the cross-linking degree of polyurethane, thereby improving flexibility, elasticity and strength, but also can utilize its own strength and wear resistance to improve the wear resistance effect.
[0061] In the preparation process of the magnesium oxide sand composite in the enhancer of Example 5, no cellulose nanocrystals and polyethylene glycol liquid were added. Compared with Example 1, the tensile strength of the elastomer prepared in Example 5 was lower than that in Example 1, the elongation at break was lower than that in Example 1, the rebound rate was lower than that in Example 1, and the abrasion amount was higher than that in Example 1; this indicates that the hydroxyl groups in the cellulose nanocrystals and polyethylene glycol liquid can not only cross-link with polyester polyols, isocyanates and other substances to improve the strength and flexibility, but also the cellulose nanocrystals can further improve the flexibility of the polyurethane elastomer. At the same time, during the casting process, polyethylene glycol 8000 can be hot-melted at 65-70°C, thereby further ensuring the cross-linking effect, so that the polyurethane elastomer has higher elasticity, flexibility and better wear resistance.
[0062] No cetearyl alcohol liquid was added during the preparation of the magnesia sand composite in the enhancer of Example 6. Compared with Example 1, the tensile strength of the elastomer prepared in Example 6 was lower than that in Example 1, the elongation at break was lower than that in Example 1, the rebound rate was lower than that in Example 1, and the abrasion amount was higher than that in Example 1. This indicates that the fatty alcohol structure of cetearyl alcohol can promote the polyurethane molecular chain to have a higher degree of rotational freedom, thereby moving more flexibly and improving the flexibility and elasticity of the polyurethane elastomer. In addition, the strength of magnesia sand and the crystalline structure of cetearyl alcohol can form microcrystalline areas in the polyurethane, further improving the flexibility, strength and wear resistance of the polyurethane elastomer.
[0063] No polyetheretherketone particles were added during the preparation of the diatomaceous earth composite in the enhancer of Example 7. Compared with Example 1, the tensile strength of the elastomer prepared in Example 7 was lower than that in Example 1, the elongation at break was lower than that in Example 1, the rebound rate was lower than that in Example 1, and the abrasion amount was higher than that in Example 1; this indicates that the polyetheretherketone particles themselves have a good dispersion and filling effect, and with their higher strength and better flexibility, the strength, flexibility and wear resistance of the polyurethane elastomer are improved.
[0064] The wear-resistant fillers in Example 8 are silicon carbide powder and aluminum oxide powder, and no polycaprolactone particles are added. Compared with Example 1, the tensile strength of the elastomer prepared in Example 8 is lower than that in Example 1, the elongation at break is lower than that in Example 1, the rebound rate is lower than that in Example 1, and the wear amount is higher than that in Example 1; this indicates that after the polycaprolactone particles are uniformly mixed with the nano-scale silicon carbide powder and aluminum oxide powder, as the curing process after pouring is solved, the polycaprolactone is gradually hot-melted, and the silicon carbide powder and aluminum oxide powder are dispersed and filled in the polyurethane network structure, thereby further improving the strength and wear resistance of the polyurethane elastomer. Polycaprolactone has a certain flexibility and can improve the flexibility of the polyurethane elastomer.
[0065] Combining Example 1 and Comparative Example 1 and Table 1, it can be seen that no reinforcing agent and wear-resistant filler are added to the raw materials of Comparative Example 1. Compared with Example 1, the elastomer prepared in Comparative Example 1 has a lower tensile strength than Example 1, a lower elongation at break, a lower rebound rate, and a higher wear amount than Example 1; indicating that the reinforcing agent and wear-resistant filler can improve the strength, flexibility, elasticity and wear resistance of the polyurethane elastomer.
[0066] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-strength cast polyurethane elastomer, characterized in that: The invention comprises the following raw materials in parts by weight: 85-100 parts of polyester polyol, 0.5-1 parts of catalyst, 2-5 parts of plasticizer, 2-5 parts of chain extender, 2-5 parts of reinforcing agent, 1-3 parts of wear-resistant filler, 30-50 parts of diisocyanate, 1-2 parts of adipic acid ester, 5-10 parts of ethanol, 0.5-1 parts of weathering agent and 0.5-1 parts of antioxidant.
2. A high-strength cast polyurethane elastomer according to claim 1, characterized in that: The reinforcing agent is composed of a magnesium oxide sand complex and a diatom sand complex in a mass ratio of 1:1-2.
3. A high-strength cast polyurethane elastomer according to claim 2, characterized in that: The magnesia sand composite is prepared by loading polyethylene glycol liquid and cellulose nanocrystals on magnesia sand and then bonding with cetearyl alcohol liquid. The mass ratio of magnesia sand, polyethylene glycol liquid, cellulose nanocrystals and cetearyl alcohol liquid is 1:0.1-0.2:0.05-0.1:0.15-0.
3.
4. A high-strength cast polyurethane elastomer according to claim 3, characterized in that: The average length of the cellulose nanocrystals is 80-200 nm, and the average particle size of the magnesium oxide sand complex is 5-10 μm.
5. A high-strength cast polyurethane elastomer according to claim 2, characterized in that: The diatom sand complex is prepared from diatom sand, N-hydroxysuccinimide composite liquid and polyetheretherketone particles in a mass ratio of 1:0.5-1:0.2-0.
5.
6. A high-strength cast polyurethane elastomer according to claim 5, characterized in that: The N-hydroxysuccinimide composite liquid is prepared from N-hydroxysuccinimide, propolis and ethanol in a mass ratio of 1:0.2-0.5:90-110.
7. A high-strength cast polyurethane elastomer according to claim 1, characterized in that: The wear-resistant filler is prepared by polycaprolactone particles loaded with silicon carbide powder and aluminum oxide powder in a mass ratio of 1:0.5-1:0.5-1. The average particle diameters of the silicon carbide powder and the aluminum oxide powder are 100-500nm, and the average particle diameter of the polycaprolactone particles is 10-20μm.
8. A high-strength cast polyurethane elastomer according to claim 1, characterized in that: The chain extender is composed of 1,4-butanediol and zinc-based tridecanol in a mass ratio of 1:0.5-1.
9. A high-strength cast polyurethane elastomer according to claim 1, characterized in that: The catalyst consists of dibutyltin dilaurate and triethanolamine in a mass ratio of 1:0.2-0.
4.
10. A method for preparing a high-strength cast polyurethane elastomer according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing polyester polyol, adipic acid ester and ethanol and stirring evenly to obtain a primary mixture; S2, adding diisocyanate, catalyst, plasticizer and chain extender to the primary mixture, treating at 50-55°C for 1-3h, and finally adding wear-resistant filler, reinforcing agent, weathering agent and antioxidant, mixing and stirring evenly to obtain a casting material; S3. The casting mold is preheated to 65-70° C., the casting material is poured into the casting mold, and the casting material is kept warm and cured for 1-2 hours, and then cooled to room temperature to obtain a finished polyurethane elastomer.